2018
DOI: 10.1080/10641963.2017.1411495
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep is responsible for the impaired nocturnal blood pressure dipping in elderly hypertensive: A cross-sectional study of elderly

Abstract: In elderly patients with hypertension, poor sleep quality individuals were more prone to reverse dipper BP rhythm. Even adjusting for the effect of known risk factors of hypertension, poor sleep may contribute to attenuated BP dipping in elderly hypertensive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Regarding the components of sleep quality, participants gave the highest mean score to sleep latency (duration needed to initiate sleep), which is consistent with the findings reported by Chen, Clark, Tsai, and Lin (2010) in heart failure patients, where hypertension was the major comorbid in their study. However, in Zhao, Fu, Ren, and Luo (2018) study, subjective sleep quality score had the highest score in different groups of blood pressure rhythm among Chinese patients with hypertension. A common sleep problem, insomnia, which has symptom of trouble initiating sleep (poor latency of sleep), through the mediation of hypertension is associated with an increased risk of cardiovascular diseases (Sofi et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…Regarding the components of sleep quality, participants gave the highest mean score to sleep latency (duration needed to initiate sleep), which is consistent with the findings reported by Chen, Clark, Tsai, and Lin (2010) in heart failure patients, where hypertension was the major comorbid in their study. However, in Zhao, Fu, Ren, and Luo (2018) study, subjective sleep quality score had the highest score in different groups of blood pressure rhythm among Chinese patients with hypertension. A common sleep problem, insomnia, which has symptom of trouble initiating sleep (poor latency of sleep), through the mediation of hypertension is associated with an increased risk of cardiovascular diseases (Sofi et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…The finding was in line with the studies done in Indonesia 35.6% [ 39 ], South Asia 34–41% [ 40 ], Italy 38.2% [ 12 ], and Jimma, Ethiopia 35.5% [ 11 ]. On the other hand, it was lower than the study done in the US 52.1% [ 41 ], China 57.1% [ 9 , 42 45 ], Brazil 55% [ 21 ], Turkey 63.3% [ 46 ], Nigeria 43.2% [ 10 , 47 ]. The discrepancy could be attributed to study design, study setting, sampling method, data collection tool, and/or procedures.…”
Section: Discussionmentioning
confidence: 79%
“…21 In the study of Zhao et al who evaluated the sleep quality of 1,006 hypertensive patients over 65 years of age with PSQI, individuals with poor sleep quality were found to be more prone to RD BP rhythm. 22 In the study of Lyu et al evaluating 368 normotensive individuals between the ages of 30-60, it was found that clinical features of insomnia and poor sleep quality are associated with non-dipping BP. 18 In Lyu et al 's study using the Wisconsin Sleep Cohort, 18 polysomnography and ABPM readings of all participants were obtained at random intervals, every 15-20 minutes during wakefulness, and every 30 minutes during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents are asked to rate, on a 4-point scale (0-3), their usual chances of dozing off or falling asleep while engaged in eight different activities. An ESS >10 points suggest the presence of excessive daytime sleepiness and results were evaluated in 5 groups [lower normal (0-5), higher normal (6-10), mild excessive (11)(12), moderate excessive (13)(14)(15), and severe excessive sleepiness (16)(17)(18)(19)(20)(21)(22)(23)(24)]. 12 ISI is a seven-item questionnaire designed as a short screening tool for insomnia.…”
Section: Methodsmentioning
confidence: 99%